Characterization of High Molecular Weight Poly(vinyl chloride) - Lithium Tetraborate Electrolyte Plasticized by Propylene Carbonate - Subramaniam, Ramesh T.; Chiam-Wen, Liew; Yee, Lau Pui; Morris, Ezra (IntechOpen, 2012)
None